PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI ORGAN GERAK MANUSIA DI KELAS V SEKOLAH DASAR - Rifmasari, Yessi; Martha, Alfroki (Jurnal Ilmiah Aquinas, 2023)
This research is motivated by several problems, namely there are several concepts in science material that require special understanding. On the materialof human movement organs because it cannot be seen directly if there is no intermediary in the formof learning media and there is no interactive multimedia learning media, especially on the material of human movement organs. Based on these problems, interactive multimedia-based learning media was developed on the material of human movement organs in grade V elementary school on theme 1 sub-theme 2 learning 2. This research was conducted at SDN 05 Sawahan Padang. The purpose of this research is to produce valid, practical, and effective learning media. This type of research is research and development (R&D) using a 4-D model (Define, Design, Development, Dissemination). The data collection instruments in this study were in the form of learning media validation sheets (for design, language, and material experts), practicality tests, and effectiveness tests. The results of the validation test for developing interactive multimedia-based learning media on human movement organs with 3 validators were categorized as very valid, the results of the practicality test by one educator and twenty-six students were categorized as very practical, and the results of the effectiveness test by twenty-six people. students are categorized as very effective. The level of validity obtained by the validity test results with the percentage of design feasibility (90%), the percentage of language (92.5%), the percentage of material (75%). The results of the practicality test by educators get an average value (95%) and the practicality results of students get an average value (98.2%). The results of the effectiveness test of twenty-six students got an average score (94.5%). Proving that interactive multimedia-based learning media on the material of human movement organs in grade V elementary school theme 1 sub-theme 2 learning 2 is declared valid, practical, effective and feasible to use